m6A Topological Transition Coupled to Developmental Regulation of Gene Expression During Mammalian Tissue Development - Li, Shanshan; Yang, Qing; Jiao, Rui; Xu, Pengfei; Sun, Yazhou; Li, Xin (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) is the most prevalent internal modification and reversible epitranscriptomic mark in messenger RNAs (mRNAs) and plays essential roles in a variety of biological processes. However, the dynamic distribution patterns of m6A and their significance during mammalian tissue development are poorly understood. Here, we found that based on m6A distribution patterns, protein-coding genes were classified into five groups with significantly distinct biological features and functions. Strikingly, comparison of the m6A methylomes of multiple mammalian tissues between fetal and adult stages revealed dynamic m6A topological transition during mammalian tissue development, and identified large numbers of genes with significant m6A loss in 5’UTRs or m6A gain around stop codons. The genes with m6A loss in 5’UTRs were highly enriched in developmental stage-specific genes, and their m6A topological transitions were strongly associated with gene expression regulation during tissue development. The genes with m6A gain around the stop codons were associated with tissue-specific functions. Our findings revealed the existence of different m6A topologies among protein-coding genes that were associated with distinct characteristics. More importantly, these genes with m6A topological transitions were crucial for tissue development via regulation of gene expression, suggesting the importance of dynamic m6A topological transitions during mammalian tissue development.